2001
DOI: 10.1046/j.1464-5491.2001.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma developing in necrobiosis lipoidica

Abstract: We describe a case of squamous cell carcinoma arising in long-standing necrobiosis lipoidica in a type 1 female diabetic patient. The tumour and the skin lesion were successfully excised and repaired with full thickness skin graft. The development of squamous cell carcinoma in association with this skin disorder is rare (only four cases reported in literature since 1966), but should be considered in chronic, non-healing and recalcitrant ulcers developing within areas of necrobiosis lipoidica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 10 publications
0
26
0
2
Order By: Relevance
“…In this respect, most of our patients showed a lack of compliance or adherence, despite the psychological strain caused by the cosmetically disfiguring ulcerations and the pain. In addition, regular follow-up is necessary because it has been shown that long-standing chronic ulcerating lesions of necrobiosis lipoidica can lead to squamous cell carcinoma owing to malignant transformation as described in several case reports (28)(29)(30). In addition, an adequate pain therapy is necessary, because all patients in our group described their ulcerations as very painful.…”
Section: Treatmentmentioning
confidence: 90%
“…In this respect, most of our patients showed a lack of compliance or adherence, despite the psychological strain caused by the cosmetically disfiguring ulcerations and the pain. In addition, regular follow-up is necessary because it has been shown that long-standing chronic ulcerating lesions of necrobiosis lipoidica can lead to squamous cell carcinoma owing to malignant transformation as described in several case reports (28)(29)(30). In addition, an adequate pain therapy is necessary, because all patients in our group described their ulcerations as very painful.…”
Section: Treatmentmentioning
confidence: 90%
“…The immune complex deposition along with enhanced platelet aggregation and coagulation plays a role. [9]An additional etiologic theory focuses on the abnormal collagen in NLD. Defective and abnormal collagen fibrils are established cause of diabetic end-organ damage and accelerated aging.…”
Section: Discussionmentioning
confidence: 99%
“…The immune complex deposition along with enhanced platelet aggregation and coagulation plays a role. [9]…”
Section: Discussionmentioning
confidence: 99%
“…Trente-cinq pour cent des patients atteints de NLD déve-lopperont des ulcérations [1]. Une NLD ancienne, comme nombre d'affections cutanées chroniques, peut se transformer en un épithélioma malpighien de la peau comme le décrivent certains auteurs [1,[9][10][11]. La biopsie des lésions de la NLD montre habituellement un épiderme normal excepté lorsqu'il y a ulcération, auquel cas, ce dernier peut être atrophié, voire absent.…”
Section: Discussionunclassified